Chronic silencing of subsets of cortical layer 5 pyramidal neurons has a long-term influence on the laminar distribution of parvalbumin interneurons and the perineuronal nets - Szabó, Florina P.; Sigutova, Veronika; Schneider, Anna M.; Hoerder-Suabedissen, Anna; Molnár, Zoltán (Journal of Anatomy, 2024)
Neural networks are established throughout cortical development, which require the right ratios of glutamatergic and GABAergic neurons. Developmental disturbances in pyramidal neuron number and function can impede the development of GABAergic neurons, which can have long-lasting consequences on inhibitory networks. However, the role of deep-layer pyramidal neurons in instructing the development and distribution of GABAergic neurons is still unclear. To unravel the role of deep-layer pyramidal neuron activity in orchestrating the spatial and laminar distribution of parvalbumin neurons, we selectively manipulated subsets of layer 5 projection neurons. By deleting Snap25 selectively from Rbp4-Cre + pyramidal neurons, we abolished regulated vesicle release from subsets of cortical layer 5 projection neurons. Our findings revealed that chronically silencing subsets of layer 5 projection neurons did not change the number and distribution of parvalbumin neurons in the developing brain. However, it did have a long-term impact on the laminar distribution of parvalbumin neurons and their perineuronal nets in the adult primary motor and somatosensory cortices. The laminar positioning of parvalbumin neurons was altered in layer 4 of the primary somatosensory cortex in the adult Snap25 cKO mice. We discovered that the absence of layer 5 activity only had a transient effect on the soma morphology of striatal PV neurons during the third week of postnatal development. We also showed that the relationship between parvalbumin neurons and the perineuronal nets varied across different cortical layers and regions; therefore, their relationship is far more complex than previously described. The current study will help us better understand the bidirectional interaction between deep-layer pyramidal cells and GABAergic neurons, as well as the long-term impact of interrupting pyramidal neuron activity on inhibitory network formation.
CRIS-Team Scopus Importer:2025-02-04
Keywords: cerebral cortex; GABAergic interneurons; layer 5; parvalbumin; perineuronal nets; Rbp4-Cre; Snap25; synaptic transmission